Policies, multi-stakeholder approaches and home-grown school feeding programs for improving quality, equity and sustainability of school meals in Northern Tanzania - Roothaert, Ralph L.; Mpogol, Hosea; Hunter, Danny; Ochieng, Justus; Kejo, Dyness (Frontiers Media, 2021)
Malnutrition among children of school-going age is a challenge of serious concern in developing countries especially Sub-Saharan Africa. Many programs focus on mothers and under-5-year-old children, leaving the school going age unattended. It has been shown that school meals can reduce school absenteeism, improve concentration in class and reduce early dropouts. In Tanzania, successful home-grown school feeding programs are localized in few areas but have not been scaled-out. The objective of this study was to analyze the policy and organizational environment which enables or promotes home-grown school feeding approaches. The study consisted of a systematic review, key informant interviews and focus group discussions in Arumeru and Babati Districts, Tanzania. In total, 21 key informant interviews with 27 participants and 27 focus group discussions with 217 participants were conducted. The results show that Tanzania lacks a clear policy on school feeding; there are no guidelines for school meal quality, participation in school feeding programs is not mandatory, leading to many students being left out and going hungry. Students in private schools tend to be better off than those in public schools in terms of provision and quality of school meals. We recommend that policies and practices are developed based on positive experiences of home-grown school feeding programs implemented in Tanzania by the World Food Programme and Project Concern International and emphasize that these policies need to be developed in a multi-sectoral manner. A conceptual framework for improving home-grown school feeding in public schools in Tanzania highlights four critical components: leadership and public awareness; operational modalities; contributions from parents; and meal diversity and nutrition. The home-grown school feeding model provides mechanisms to improve diversity of meals and their nutritional value, increase participation of communities and inclusion of students. Parents will still be responsible for the largest part of food supplies, but the model also requires participation of multiple stakeholders, and provision of natural resources such as land and water by the local government for production of nutritious food for young students. Minimum levels of social protection are recommended to ensure that no student is denied school meals.